Quality of Life in Lung Transplantation - Singer, Jonathan P.; Singer, Lianne G. (Seminars in Respiratory and Critical Care Medicine, 2013)
Improving health-related quality of life is an important goal of lung transplantation. This review describes background concepts, including definitions, measurement and interpretation of health-related quality of life (HRQL), and other patient-reported outcomes. Lung transplantation is associated with dramatic and sustained improvements in HRQL, particularly in measures of physical health and functioning. Physical rehabilitation may augment the early improvements in HRQL, whereas bronchiolitis obliterans syndrome and psychological conditions have a negative impact. More research is needed, particularly longitudinal, multicenter studies, to better understand the trajectory and determinants of HRQL after lung transplantation, and the impact of targeted interventions to improve HRQL.
Keywords: lung transplantation; health-related quality of life; utility; disability; patient-reported outcomes